2013
DOI: 10.1002/anie.201308873
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Synthesis of Unsymmetrical Unsaturated N‐Heterocyclic Carbene Precursors and Their Related Transition‐Metal Complexes

Abstract: A low-cost, modular, and easily scalable multicomponent procedure affording access in good yields and excellent selectivity (up to 93%) to a wide range of (a)chiral unsymmetrical 1-aryl-3-cycloalkyl-imidazolium salts is disclosed. Electronic and steric properties of the corresponding unsymmetrical unsaturated N-heterocyclic carbene (U2-NHC) ligands were evaluated and evidenced strong electron donor ability, high steric discrimination, and modular steric demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 45 publications
2
45
0
Order By: Relevance
“…This abnormal behavior should certainly be attributed to the special properties of the newly developed unsymmetrical NHC ligands. [8] Indeed, 1-aryl-3-cycloalkylimidazol-2-ylidenes combine strong electron richness with high steric discrimination between the flexible aliphatic and bulky aromatic groups. [9,10] Analysis of the maps reported in Figure 2 also indicated that the cyclododecyl fragment minimized the steric hindrance around the metal with a buried volume % (V bur ) of 29.7 relative to the classical IMes ligand, with a V bur of 31.3 ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This abnormal behavior should certainly be attributed to the special properties of the newly developed unsymmetrical NHC ligands. [8] Indeed, 1-aryl-3-cycloalkylimidazol-2-ylidenes combine strong electron richness with high steric discrimination between the flexible aliphatic and bulky aromatic groups. [9,10] Analysis of the maps reported in Figure 2 also indicated that the cyclododecyl fragment minimized the steric hindrance around the metal with a buried volume % (V bur ) of 29.7 relative to the classical IMes ligand, with a V bur of 31.3 ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…[7] With the aim of gaining rapid access to a wide variety of unsymmetrical NHC precursors, we recently developed a multicomponent methodology that afforded N,N'-disubstituted imidazolium salts in a single step. [8] Notably, this revisited strategy of Arduengo appeared extremely efficient in the scalable preparation of 1-aryl-3-cycloalkylimidazolium salts with excellent selectivity (up to 93 %), far beyond the expected 1:2:1 statistical ratio. As a representative example, 1-mesityl-3-cyclododecylimidazolium salt 1 was prepared with 93 % selectivity and 80 % yield on a 60 g scale.…”
Section: Introductionmentioning
confidence: 99%
“…Besides chiral amines, amino alcohols 29 were also utilized in the synthesis of C 2 -symmetric gold(I) complexes 34. The respective NHC precursors 33 were obtained via a one-pot protocol [39,75] and were subsequently transformed into gold complexes by the reaction with AuCl•SMe 2 in acetone, mediated by K 2 CO 3 . However, the yield was strictly dependent on the substituents.…”
Section: Cyclic C 2 -Symmetric Gold(i) Complexesmentioning
confidence: 99%
“…Catalysts 2019, 9, A straightforward approach to imidazolium salts 112 and gold(I) complexes 113 has recently been developed by Toste (Scheme 17) [74]. Implementing Baslé and Mauduit's protocol [39,75], the authors have prepared a series of C1-symmetric NHC precursors via an elegant one-pot protocol, directly from chiral β-amino alcohols 29, mesityl amine (110), glyoxal (30), and paraformaldehyde (31). The developed protocol includes two experimentally common steps.…”
Section: Scheme 10mentioning
confidence: 99%
“…Therefore, despite the efficiency contributed by the designed NHC-based catalyst 1, the development of a lower-cost catalyst appeared necessary to extend the validity of the technology to a large-scale process. Fortunately, during the course of this project, we developed a one-step multicomponent synthesis of unsaturated unsymmetrical NHC ligands bearing a cycloalkyl side chain 26 that could provide a cost-effective alternative to the multi-step synthe-sis of their saturated ligand analogues. Thanks to the potency of this ligand synthesis, catalysts 6 and 7 (bearing a cyclododecyl and a cyclopentyl moiety respectively) could be prepared 27 and evaluated in the self-metathesis reaction of 1octene under the standard conditions (Table 4).…”
Section: Table 1: Self-metathesis Of 1-octene Catalyzed By Complexes mentioning
confidence: 99%